Current Understanding of Periodontal Etiopathogenesis and Precision Dentistry: Miles to go before we Sleep - Balu, Pratebha; Ramkumar , Narayane; Jagadeesan, Monica (Research Highlights in Disease and Health Research Vol. 6, 2023)
Periodontal disease or periodontitis is a complex multifactorial chronic inflammatory disease of the periodontium - the supporting structure of the tooth. Periodontitis leads to destruction of the connective tissues as well as alveolar bone finally leading to tooth mobility and tooth loss thereby affecting quality of life of the individual. Apart from tooth loss it also impacts systemic health of the individual and is a risk factor/ modifying factor associated with diabetes mellitus, cardiovascular diseases, pre-term low birth weight babies in pregnant women, PCOS, rheumatoid arthritis, Alzheimer disease and oral cancer. The understanding of factors responsible for periodontal disease is a cumulative influence by genetic, environmental, microbial and host-immune response factors. However it appears that periodontal disease is the net effect of the immune response and the inflammatory processes, not the mere presence of the bacteria, based on available evidence. Currently the understanding of periodontal pathogenesis is that, even though microorganisms initiate periodontal disease, perpetuation and progression of disease is the net result of regulation of immune-inflammatory responses. Immune–inflammatory mechanisms governs patient susceptibility and is modified by environmental factors. Despite extensive research and information on etiopathogenesis of periodontitis, currently periodontal therapy for all forms and severity of periodontitis remain the same. The reason is that the clinical and radiographic parameters used for diagnosis and assessment of periodontal outcome of therapy such as Probing pocket depth, clinical attachment loss and bone loss only depict past disease activity. The mediators of inflammation however have a promising potential to serve as biomarkers of current periodontal activity, disease progression and treatment efficacy indicators. Unfortunately, till date there are no biomarkers that are accurate or precise enough to monitor periodontal disease initiation or progression. No biomarker has yet been verified for diagnostic use in periodontology. Since biomarkers are the foundation of precision medicine, its application is still well behind schedule. Precision medicine is based on the combination of clinical parameters and biological markers that reflect the underlying biological processes. This enables highly accurate prediction of periodontal disease susceptibility, early diagnosis, prognosis, and planning of the most suitable and secure treatment approach to address the needs of specific patients which is the way forward.